2020
DOI: 10.21037/med-20-28
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pathological analysis on endobronchial ultrasound diagnostic accuracy

Abstract: Endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive procedure used for lung cancer diagnosis and staging. Several aspects, including pathological analysis, may impact on its diagnostic accuracy. Differences in diagnostic accuracy between the different specimen processing techniques have not been demonstrated. Cytological slides are generally adequate for diagnosis, subtyping and genotyping. However, some pathological laboratories may require cell blocks or histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…During EBUS‐TBNA, three to four passes for each target constitute the recommended least requirement. Here, ROSE may reduce the passes for molecular tests and the number of further invasive procedures 18 . A retrospective review of 516 EBUS‐FNA procedures revealed that ROSE assessment of the first 5 passes during the EBUS‐FNA could provide similar adequacies compared to total ROSE judgment of all punctures 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During EBUS‐TBNA, three to four passes for each target constitute the recommended least requirement. Here, ROSE may reduce the passes for molecular tests and the number of further invasive procedures 18 . A retrospective review of 516 EBUS‐FNA procedures revealed that ROSE assessment of the first 5 passes during the EBUS‐FNA could provide similar adequacies compared to total ROSE judgment of all punctures 19 .…”
Section: Discussionmentioning
confidence: 99%
“…for molecular tests and the number of further invasive procedures. 18 A retrospective review of 516 EBUS-FNA procedures revealed that ROSE assessment of the first 5 passes during the EBUS-FNA could provide similar adequacies compared to total ROSE judgment of all punctures. 19 According to a review on 618 subjects, the employment of ROSE during EBUS-TBNA necessitated significantly fewer needle passes.…”
Section: Pathological Materials Triage and Adequacy For Ancillary Testsmentioning
confidence: 99%
“…ROSE is a widely used and effective diagnostic procedure during a needle aspiration biopsy of different organs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In the field of thoracic pathologies, several studies have demonstrated the utility of ROSE during both transbronchial and percutaneous needle aspiration techniques [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Even if some works failed to demonstrate that ROSE increases the sensitivity during cTBNA or EBUS-TBNA [ 15 , 16 ], there is robust evidence that ROSE may significantly reduce the need for additional passes and the complication rate, most importantly improving the adequacy of the samples addressed to molecular chacaterization of mandatory predictive biomarkers in non-small cell lung cancer [ 6 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the C1–C5 system is that it mainly provides information about the diagnostic value of the sample, and in the era of tailored therapies for lung cancer, the operator should also have information about the adequacy of the sampled material in view of the subsequent tumor genotyping for predictive molecular biomarkers. ROSE may ensure the collection of adequate material for molecular profiling [ 1 ]. In a randomized controlled trial that compared EBUS-TBNA performed without and with ROSE, Trisolini et al showed that the use of ROSE increased the percentage of adequate samples obtained by EBUS-TBNA for molecular profiling [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation